A novel step-up/step-down DC-DC converter based on flyback and SEPIC topologies with improved voltage gain - Khaled A. Mahafzah; Hana A. Rababah (Institute of Advanced Engineering and Science, 2023)
A novel step-up/step-down DC-DC converter with improved voltage gain characteristics is suggested in this paper. The proposed converter combines flyback and single-ended primary inductance converter (SEPIC) converters. The voltage control loop design is simplified due to the use of only a single controlled switch. It has been discussed how switch duty cycle affects voltage gain. This relationship demonstrates that the proposed converter voltage gain is improved compared with flyback and SEPIC converters. However, compared to flyback and SEPIC converters, it has a higher voltage gain at any given duty cycle. The proposed converter operation is thoroughly discussed, the associated equations are derived, and its parameters are expertly designed. Moreover, it is designed to supply a DC load of 2.5 kW, 500 V, and 5 A. The proposed converter efficiency exceeds 84% under rated load conditions. Additionally, it is also presented as an adapter for electric vehicles. The waveforms associated with the simulation of the converter across the universal line voltage of 110-260 Vrms are shown. At both line voltages, the total harmonics distortions (THDs) of the line current are 17.12% and 27.26%, respectively. MATLAB/Simulink is utilized for validation in order to validate the topology for different applications.